1994
DOI: 10.1007/bf00188569
|View full text |Cite
|
Sign up to set email alerts
|

Flexor tendon repair in perfect safety

Abstract: When summarising the principles behind successful zone II flexor tendon repair surgery, technical perfection through experience appears of prime importance. The authors present a device intended to allow inexperienced surgeons to gain the necessary skill in a laboratory environment. The detail of the practicalities regarding construction and use of this "surgical training simulator" are specifically addressed. Conclusions are drawn after four years of experience with the device, and extension of the simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Historically tendon repair techniques for the hand were taught using divided pig tendons either in vivo or secured on a cork board [12]. Flemming et al made the first reported tendon repair simulator in 1994; they used a pediatric Foley catheter to simulate a flexor tendon injury with wooden pieces and tape simulating phalanx and pulley system, respectively, in the finger [13] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Historically tendon repair techniques for the hand were taught using divided pig tendons either in vivo or secured on a cork board [12]. Flemming et al made the first reported tendon repair simulator in 1994; they used a pediatric Foley catheter to simulate a flexor tendon injury with wooden pieces and tape simulating phalanx and pulley system, respectively, in the finger [13] (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six simulators were physical synthetic structures, the injury could be repaired with visual and tactile feedback on completion, 13–15,17–19,21–24,26,27,29,30,32,33,35–37,40–59,61–63,65–67,70 and 17 of the simulators reacted with virtual visual representations, such as bleeding or real-time x-ray of a nail insertion, all of which could be erased for the next user; most of these were digitally based 16,20,25,28,31,34,38,39,60,64,68,69,71–75 . Eight studies referred to the features of increasing difficulty of the task built into the simulator 34,49–52,58,65,68,71 . This usually involved, for example, decreasing the size of a vessel and therefore difficulty of repair or choosing a more difficult part of the bone for fracture repair.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, 11 of the studies described full-task trainers 35,38,40,55,65,66,68,70,72–75 and 52 described a part-task trainer who focused on a particular part of the procedure 13–34,36,37,39,41–54,56–64,67,69,71,73 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations